Designing a new cross-linkable cohesin complex for studying cohesin`s interaction with DNA - Uluocak, P (2012)
Sister chromatid cohesion is essential for accurate chromosome segregation. Cohesion is generated by cohesin, a conserved multi-subunit protein complex composed of four core subunits: Smc1, Smc3, Scc1, and Scc3. Cohesin holds sister chromatids together in mitotic cells starting from S-phase, when DNA replicates, until their separation at the onset of anaphase where its Scc1 subunit is cleaved. In budding yeast, most Scc1 is destroyed by cleavage at anaphase and is only re-synthesised in late G1, whereupon it associates with the unreplicated chromatin. Although sister chromatid cohesion is known to be mediated by a topological interaction of cohesin complexes around sister DNAs, the nature of cohesin`s interaction with chromatin before DNA replication remains to be elucidated. My project aims to develop a new system in order to find out whether ‘non-cohesive’ cohesin interacts with chromatin topologically. This is important for two main reasons. Firstly, understanding the physical nature of cohesin’s interaction with chromatin before DNA replication is essential for determining how cohesion is established during DNA replication. Another reason is that most cohesin in multicellular organisms is associated with the unreplicated chromatin of post mitotic cells where it regulates transcription. How cohesin mediates gene expression is unknown. Understanding how cohesin binds unreplicated chromatin may therefore bring insights into the mechanisms by which cohesin complex performs its non-canonical functions. In order to address this, we needed a situation where cohesin is already loaded onto chromosomes, but either DNA replication or cohesion establishment is prevented. Therefore, we used a temperature sensitive allele of Eco1 (required for establishment of cohesion). Quantitative measurement of cohesin levels on chromosomes in either wild type allele or temperature sensitive allele of Eco1 showed that the amount of cohesin associated with centromeric and inner pericentromeric regions in both strains are almost indistinguishable from each other throughout the whole cell cycle. Despite normal levels of cohesin, we confirmed by minichromosomal assay that no sister chromatid cohesion is established in the absence of functional Eco1 protein. If “non-cohesive” cohesin interacts with the chromatin in a topological manner when there is no sister chromatid cohesion, then its association with chromatin should be resistant to denaturing conditions in the presence of a modified version of the cohesin complex that can be covalently circularized. To test this prediction, a cross-linkable cohesin molecule was needed, which should be resistant to SDS denaturation and should not have major cohesion defects due to the modifications making it to be cross-linkable. The previously created cross-linkable cohesin molecule had cohesion defects due to the presence of Smc3-Scc1 fusion protein. In addition, this fusion alone could bypass the requirement for Eco1, and therefore we could not test how “non-cohesive” cohesin interacts with chromatin, using this version of cross-linkable cohesin complex. We tried two different methods to conditionally close Smc3/Scc1 interface in a way resistant to protein-denaturants and create a new cross-linkable cohesin complex. In our first attempt, the C-terminus of Smc3 and the N-terminus of Scc1 were fused to FRB and FKBP12 respectively, proteins that can form a complex upon addition of rapamycin. Crystal structure of the ternary complex of FKP12/rapamycin/FRB enabled us to design cysteine pairs for the crosslinking of FRB and FKBP12 only in the presence of rapamycin. A more efficient in vivo crosslinking was achieved between the Smc3 and Scc1 in our second attempt. Amino acids within the coiled coil region of Smc3 were replaced by the unnatural photo-cross-linkable amino acid ρ-benzoyl-phenylalanine that can be induced to form covalent bonds with neighbouring proteins (T.Gligoris, unpublished data). Photo and chemically cross-linkable interfaces of cohesin were then integrated with each other to generate a new version of cross-linkable cohesin molecule.